Caliphate Redefined : The Mystical Turn in Ottoman Political Thought - Yılmaz, Hüseyin (Book collections on Project MUSE., 2018)
The medieval theory of the caliphate, epitomized by the Abbasids (750-1258), was the construct of jurists who conceived it as a contractual leadership of the Muslim community in succession to the Prophet Muhammed's political authority. In this book, the author traces how a new conception of the caliphate emerged under the Ottomans, who redefined the caliph as at once a ruler, a spiritual guide, and a lawmaker corresponding to the prophet's three natures. Challenging conventional narratives that portray the Ottoman caliphate as a fading relic of medieval Islamic law, the book offers a novel interpretation of authority, sovereignty, and imperial ideology by examining how Ottoman political discourse led to the mystification of Muslim political ideals and redefined the caliphate. This work illuminates how Ottoman Sufis reimagined the caliphate as a manifestation and extension of cosmic divine governance. The Ottoman Empire arose in Western Anatolia and the Balkans, where charismatic Sufi leaders were perceived to be God's deputies on earth. The author traces how Ottoman rulers, in alliance with an increasingly powerful Sufi establishment, continuously refashioned and legitimated their rule through mystical imageries of authority, and how the caliphate itself reemerged as a moral paradigm that shaped early modern Muslim empires. This book presents a comprehensive study of premodern Ottoman political thought to offer an extensive analysis of a wealth of previously unstudied texts in Arabic, Persian, and Ottoman Turkish.